Laparoscopic sacrocolpopexy as the mainstay management for significant apical pelvic organ prolapse (LAP) study. (January 2020) - Kalis, Vladimir; Smazinka, Martin; Rusavy, Zdenek; Blaganje, Mija; Havir, Martin; Havelkova, Linda; Ismail, Khaled
Abstract: Study objectives: The primary aim of this study was to assess the clinical feasibility of a policy where laparoscopic sacrocolpopexy (LSC) is the default procedure for the management of a significant apical pelvic organ prolapse (a-POP). As a secondary aim, we wanted to evaluate LSC outcomes in relation to women's preoperative assessment of their surgical fitness using the American Society of Anesthesiologists physical status (ASA-PS) categorization. Design: Retrospective cohort study. Setting: A university affiliated urogynecology center. Methods: All women with symptomatic a-POP (C ≥ -1) who attended the urogynecology clinic between the 1 st of January and the 31 st of December 2016 and had their surgery by the 31 st of May 2017 were included in the study. In our unit, routine follow-up appointments are arranged at 3 and 12 months post LSC. Interventions: Perioperative and mesh-related complications were assessed based on the Dindo-Clavien and IUGA/ICS classifications respectively. The preoperative outcome measures included Pelvic Organ Prolapse Quantification (POP-Q) stage, Pelvic Floor Distress Inventory (PFDI) and ASA-PS score. At follow-up women were asked to complete a PFDI, Patient Global Impression of Improvement (PGI-I), had their POP-Q staging and ultrasonographic assessment of mesh position and placement. The above measures are routinely collected as part of our standard practice. A preoperative ASA-PS score of <3 was used as a cut-off to dichotomies participants into low and high risk. Main results: A total of 220 women attended our center during the study period because of POP. Of these, 146 women were diagnosed with a significant a-POP and 142 (97.2 %) women opted for a surgical repair. Of the 142 women, 128 (90.1 %) were deemed suitable for a type of LSC and 121 had their surgery before the 31 st of May 2017. There were no statistically significant differences in any of our collected perioperative, clinical, patient reported or ultrasonographic outcome measures when comparing women with ASA-PS scores of <3 or ≥3. Conclusion: In a specialized urogynecology healthcare setting, it is feasible and safe to rely on LSC as the mainstay surgical procedure for the repair of a significant a-POP. However, it is imperative to ensure that technical skills and equipment requirements are fulfilled and maintained.